2022
DOI: 10.3389/fmicb.2022.1042923
|View full text |Cite
|
Sign up to set email alerts
|

Chronic alcohol-induced dysbiosis of the gut microbiota and gut metabolites impairs sperm quality in mice

Abstract: Studies have indicated that the ethanol exposure impairs the gut microbiota, At the same time, high levels of alcohol exposure damage sperm in mice. However, whether the gut microbiota is involved in mediating the effects of alcohol on sperm quality remains unclear. This study aimed to assess the effect of chronic alcohol consumption on intestinal microbiota in mice and analyze the potential pathophysiological effect of altered intestinal microbiota on sperm quality. We established a mouse model of chronic alc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 77 publications
0
7
0
Order By: Relevance
“…Gut microbes and their metabolites alter levels of various inflammatory cytokines ( 47 49 ). A study has shown that chronic alcohol consumption disrupts the gut microbial environment, leading to significant decreases in the levels of some of these key gut microbes (e.g., Helicobacter, a genus of Bacteroides), which in turn alters the body’s microenvironment, resulting in altered levels of inflammatory cytokines in the body, and ultimately an increased risk of infertility ( 50 ). Despite existing knowledge linking the gut microbiome to inflammatory cytokine levels, the exact mechanisms by which the gut microbiome affects inflammatory cytokine levels, especially HGF, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Gut microbes and their metabolites alter levels of various inflammatory cytokines ( 47 49 ). A study has shown that chronic alcohol consumption disrupts the gut microbial environment, leading to significant decreases in the levels of some of these key gut microbes (e.g., Helicobacter, a genus of Bacteroides), which in turn alters the body’s microenvironment, resulting in altered levels of inflammatory cytokines in the body, and ultimately an increased risk of infertility ( 50 ). Despite existing knowledge linking the gut microbiome to inflammatory cytokine levels, the exact mechanisms by which the gut microbiome affects inflammatory cytokine levels, especially HGF, remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has demonstrated the involvement of gut microbiota in alcohol consumption, [ 8 10 ] and the disruption of gut microbiota through antibiotics has been shown to increase ethanol consumption in mice [ 33 ]. In agreement with this study, we found that Abx treatment significantly increased voluntary ethanol consumption levels in a binge-like ethanol drinking paradigm in mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in the microbiome and alcohol research have shown that alcohol consumption can influence [ 6 ] or be influenced by the gut microbiome [ 7 ]. Acute or chronic alcohol consumption breaks down the homeostasis of gut microbiota, resulting in an overgrowth of harmful bacteria and a reduction in beneficial bacteria [ 8 10 ]. Dysbiosis of gut microbiota has been highlighted in the progression of alcoholic liver diseases [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…An important risk factor for male infertility is poor sperm quality. In addition to overweight (Salas-Huetos et al, 2021 ), substance abuse (Gundersen et al, 2015 ), and testicular inflammation (Bryan et al, 2020 ), poor lifestyle habits such as smoking (Sharma et al, 2016 ), alcohol consumption (Li et al, 2022 ), and consumption of sugary beverages (Nassan et al, 2021 ) can affect sperm quality.…”
Section: Introductionmentioning
confidence: 99%